COOPERATIVE LEARNING TYPE TEAMS GAMES TOURNAMENT ON RESPIRATORY SYSTEM LESSON TO INCREASE THE STUDENTS LEARNING ACTIVENESS - I Dewa Putu Juwana; Putu Diah Kirana Purnama Dewi (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study aimed to determine implementation of cooperative learning of the Teams Games Tournament type on respiratory system lesson to the students learning activeness of class XI MIPA 2 SMA Negeri 1 Kuta Utara. The type of this research was classroom action research. The dependent research variable was learning activeness using an observation sheet in the form of a questionnaire. The data were analysed using quantitative descriptive data analysis with proportions. The results of this study indicated that in the implementation of the first cycle, the average achievement of student activeness was 63.48%. During the implementation of cycle II, the average student activeness achievement increased by 19.41% from cycle I to 82.89%. In cycle II, 38 students got very active and 7 students got active. Thus, it could be interpreted that applying the cooperative learning model of the Teams Games Tournament (TGT) type could increase student learning activeness in class XI MIPA 2 SMA Negeri 1 Kuta Utara especially on respiratory system lesson.